The Effect of Thermal Treatment on the Characteristics of Porous Ceramic-Based Natural Clay and Chitosan Biopolymer Precursors - Indah Raya; Rachmat Triandi Tjahjanto; Rizal Irfandi; Harningsih Karim; Susilo Sudarman Desa; Abd Rahman; Suriati Eka Putri; Ahyar Ahmad (Universitas Gadjah Mada, 2023)
This study was conducted to determine the role of thermal treatment on the crystallinity and pore characteristics of porous ceramic, which was prepared from natural clay (NC) and chitosan (CS) biopolymer using the gel casting method. CS was used as an environmentally friendly pore-forming agent. The applied temperature treatment was based on thermal analysis (TGA/DTA) results and followed a sintering temperature of 900 to 1100 °C. The results showed that at sintering temperatures from 900 to 1000 °C, the crystallinities of the ceramic decrease (from 76.06 to 74.06%) and the crystallite size decreases (from 35.71 to 34.47 nm) while the lattice strain increases (calculated from the Full Width at Half Maximum (β) of the diffraction peak). The highest porosity of ceramic occurred at a sintering temperature of 1000 °C of 37.82 ± 0.19, but the formation of heterogeneous microstructure was observed. The resulting pore size for all temperature treatments was almost mesoporous (19.1 Å). Based on the results obtained, it is emphasized that the sintering temperature can be used to adjust the porosity and microstructure of porous ceramics.